Defected ground structure loaded with meandered lines for decoupling of dual-band antenna. Issue 13 (2nd September 2019) - Li, Qinlong; Abdullah, Muhammad; Chen, Xiaoming
ABSTRACT: A defected ground structure (DGS) loaded with meandered lines is proposed to reduce mutual coupling of a dual-band planar multiple-input multiple-output (MIMO) antenna. To verify the effectiveness of a proposed DGS, a dual-band MIMO antenna is designed and manufactured. The antenna consists of two planar-inverted F-antenna (PIFA) elements printed symmetrically for dual-band operation. The DGS is placed between these two PIFA elements to reduce mutual coupling. The DGS consists of a slot and a pair of meander lines inside it, hence generating two independently tuneable resonances. A two element MIMO antenna is studied using computer simulation and a final design is manufactured. The antenna is measured using the Satimo Starlab system. Simulation results show that the MIMO antenna has the bandwidths (S11 & S22 <−10 dB, S21 & S12 <−15 dB) of 1.56–2.71 GHz (1.15 GHz or 54%) and 4.82–5.9 GHz (1.08 GHz or 20%) in the lower and higher frequency bands, respectively. Measurement results agree well with the simulation.